2012
DOI: 10.1038/nature11001
|View full text |Cite
|
Sign up to set email alerts
|

A novel putative auxin carrier family regulates intracellular auxin homeostasis in plants

Abstract: The phytohormone auxin acts as a prominent signal, providing, by its local accumulation or depletion in selected cells, a spatial and temporal reference for changes in the developmental program [1][2][3][4][5][6][7] . The distribution of auxin depends on both auxin metabolism (biosynthesis, conjugation and degradation) [8][9][10] and cellular auxin transport [11][12][13][14][15] . We identified in silico a novel putative auxin transport facilitator family, called PIN-LIKES (PILS). Here we illustrate that PILS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
406
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(439 citation statements)
references
References 35 publications
13
406
0
Order By: Relevance
“…In the present study, it has found that, all the OsPILS (OsPILS1, OsPILS2, OsPILS6a, OsPILS6b, OsPILS7a and OsPILS7b) proteins contains short hydrophilic loop and hence supposed to be endomembrane localized (Table 3). Finding presented in this manuscript also closely matches with finding of Barbez et al, (2012). In the phylogenetic tree, the short transmembrane domain containing proteins OsPIN5 and AtPIN5 are present very closely with OsPILS proteins (Figure 6).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In the present study, it has found that, all the OsPILS (OsPILS1, OsPILS2, OsPILS6a, OsPILS6b, OsPILS7a and OsPILS7b) proteins contains short hydrophilic loop and hence supposed to be endomembrane localized (Table 3). Finding presented in this manuscript also closely matches with finding of Barbez et al, (2012). In the phylogenetic tree, the short transmembrane domain containing proteins OsPIN5 and AtPIN5 are present very closely with OsPILS proteins (Figure 6).…”
Section: Resultssupporting
confidence: 88%
“…Maximum of OsPILS genes were found to be subcellularly localized either in endoplasmic reticulum and vacuoles (Table 3). Presence of OsPILS proteins in endoplasmic reticulum/vacuoles that facilitates auxin accumulation inside the cells seems to contribute the possibility of compartmentalized regulation of auxin metabolism (Barbez et al 2012). It could be period in auxin treated root tissues (Figure 7) respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, short PINs (PIN5, 6,8) are localized in the endomembrane system (most likely the endoplasmic reticulum (ER)) and appear to function in intracellular auxin transport and homeostasis [32,33]. Recently, a second family of ER-localized auxin transporters, called PILS (for PIN-LIKES), was also shown to regulate auxin homeostasis [34], although their role in auxin transport is less clear. AUX1/LAX and ABCB proteins are plasma membrane localized like long PINs, but are most often apolar (reviewed in Ref.…”
Section: Auxin Transport Across Biological Membranesmentioning
confidence: 99%